Long-Term Survival of a Patient with Recurrent Dedifferentiated High-Grade Liposarcoma of the Retroperitoneum Under Adjuvant Treatment with Viscum album L. Extract: A Case Report. (February 2021) - Reynel, María; Villegas, Yván; Werthmann, Paul G.; Kiene, Helmut; Kienle, Gunver S.
Retroperitoneal sarcomas are rare. Dedifferentiated liposarcomas (DDLs) are high-grade tumors with a high propensity for local recurrence and metastasis and are associated with reduced survival. Radical resection remains the standard treatment of sarcomas. Meanwhile, Viscum album L. extract (VAE) is used in cancer patients owing to its cytostatic and immunomodulating effects and to its ability to improve patients' quality of life. Case Presentation: A 68-year-old male patient underwent a resection of a DDL (T2 N0 M0, FNCLCC grade 2, stage IIIA) in the retroperitoneum. Three months after this first surgery, a recurrence occurred, and was treated with neoadjuvant and adjuvant doxorubicin plus ifosfamide and surgery (resection). A second recurrence—11 months after the second surgery—was treated with surgery and radiotherapy. The patient then began to undergo VAE treatment (0.2 mg-2 mg, subcutaneously, thrice a week). After the VAE treatment was initiated, the patient reported improved quality of life. A third recurrence—12 months after the third surgery—was treated with surgery, radiotherapy, and with an increased dose of VAE (20 mg). Sixty-nine months (5.8 years) after the fourth surgery a fourth recurrence occurred. It was again treated with surgery, along with a month of intravenous VAE infusions and subsequent subcutaneous VAE (20 mg) treatment. Finally, a fifth recurrence—5 months after the fifth surgery—was treated with subcutaneous and intravenous VAE applications and eribulin. The patient died 11 months after the last recurrence; he received a total of 103 months (8.6 years) of VAE treatment and achieved 10.5 years of survival. Conclusion: The case presented herein shows a long-time survival and a prolonged recurrence-free interval in a patient with retroperitoneal DDL treated with surgery, chemotherapy, radiotherapy, and VAE injections. On the basis of the antitumoral and immunomodulating effects of VAE and on the reported prolonged survival of VAE-treated patients with other types of tumors, the adjunct VAE treatment is presumed to have contributed to the favorable outcome. Regarding the clinical relevance of VAE treatment, further investigations are needed.